2021
DOI: 10.1186/s12951-021-00814-7
|View full text |Cite|
|
Sign up to set email alerts
|

Advances in the development paradigm of biosample‐based biosensors for early ultrasensitive detection of alzheimer’s disease

Abstract: This review highlights current developments, challenges, and future directions for the use of invasive and noninvasive biosample-based small biosensors for early diagnosis of Alzheimer’s disease (AD) with biomarkers to incite a conceptual idea from a broad number of readers in this field. We provide the most promising concept about biosensors on the basis of detection scale (from femto to micro) using invasive and noninvasive biosamples such as cerebrospinal fluid (CSF), blood, urine, sweat, and tear. It also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 208 publications
0
12
0
Order By: Relevance
“…In AD, although cerebrospinal fluid biomarkers are the most well-researched and widely accepted, blood biomarkers show greater prospects in the diagnosis of AD. The widespread application of blood biomarkers relies on the development and application of ultra-sensitive detection methods ( Karki et al, 2021 ), so their accurate detection and quantification will greatly facilitate current and future diagnostic and therapeutic efforts. This review introduces the application of peptides or peptide mimics of different sources and functions as identification elements or carriers of biosensors or molecular probes in the highly sensitive detection and diagnosis of AD.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…In AD, although cerebrospinal fluid biomarkers are the most well-researched and widely accepted, blood biomarkers show greater prospects in the diagnosis of AD. The widespread application of blood biomarkers relies on the development and application of ultra-sensitive detection methods ( Karki et al, 2021 ), so their accurate detection and quantification will greatly facilitate current and future diagnostic and therapeutic efforts. This review introduces the application of peptides or peptide mimics of different sources and functions as identification elements or carriers of biosensors or molecular probes in the highly sensitive detection and diagnosis of AD.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…However, the relationships regrading Aβ40 and Aβ42/40 between plasma and CSF were not found in our study, which were inconsistent with the results of another study by Janelidze et al They demonstrated that Aβ40 and Aβ42/40 in plasma were also in slightly positive correlation with those in CSF. Besides the fact that the samples were of a limited size in our study, the most important reason was that the production and transport of plasma Aβ peptides were complicated and the measurement was interfered by in vivo and in vitro factors, , even with the ultrasensitive technology adopted.…”
Section: Resultsmentioning
confidence: 99%
“…There are some ways to solve these challenges (Table 1 ). First, developing ultrasensitive technologies could improve the detection ranges of plasma biomarkers, and newly-exploited antibodies are more specific and sensitive in capturing biomarkers [ 34 , 35 ]. Advanced methods for concentrating biomarkers in blood could also resolve the dilution effect.…”
Section: Establishment Of the Peripheral A-t-n-x Frameworkmentioning
confidence: 99%